Analisis Faktor yang Mempengaruhi Motivasi Belajar Mahasiswa (Studi pada Pembelajaran Mahasiswa di Masa Pendemi Covid 19) - Yenti, Wildarma; Sofya, Rani (Universitas Negeri Padang, 2024)
The aim of this study is to identify 1) the variables that influence students' motivation to learn during online courses in economics. 2) the main elements that affect students' motivation to learn when they are enrolled in online courses. This type of research is quantitative descriptive research. The sample strategy was proportional random sampling. With a selected sample of 75 students, the study's population consisted of economic education students enrolled in Padang State University's Faculty of Economics in the academic years 2018–2019–2020. Both primary and secondary data were used. A questionnaire is used to collect data. Descriptive analysis and factor analysis are the analytical techniques employed. Four factors—physiological, environmental, student competency, and non-social—have an impact on learning motivation, according to the findings of factor analysis.